Reflections on direct and indirect strategies of politeness in g. B. Shaw’s pygmalion: A satire on conventionalities of politeness - Do, Thu Huong (H. : ĐHQGHN, 2019)
This study aims at investigating male and female strategies of directness and indirectness manifest in the speech of the characters in the play Pygmalion by George Bernard Shaw. In the light of politeness theory by Brown and Levinson (1978), the realizations of direct and indirect strategies of politeness are associated with two types of strategies of face threatening acts (FTAs), namely bald-on-record and offrecord strategies. The off-record strategy, which is the main focus of the study, is examined in relation to various sub-strategies of indirectness which are described in terms of the Gricean conversational maxims (i.e. Quantity, Quality, Relevance and Manner). These sub-strategies include the use of metaphors, irony, rhetorical questions, understatements and overstatements. A statistical survey is conducted on the frequencies of two politeness indicators, namely the bald-on-record strategies and tentativeness devices employed by the characters from different social classes in the play. The methodology of qualitative analysis employed in this study is based on Brown & Levinson’s theoretical framework of politeness with the main focus on the two components of communication: gender and social classes. In the play, the gap between the high and low classes in the late 19th century British society is manifest in such differences of language use as phonetics, lexis, grammar, and pragmatics